Implementasi Manajemen Berbasis Sekolah Dalam Pengelolaan Kurikulum Merdeka Di SMP Negeri 8 Lubuklinggau - Supriyanti; Nur Sasongko , Ra; Sumarsih (Manajer Pendididikan, 2024)
The purpose of the study was to describe the implementation of school-based management in managing the independent curriculum at SMP Negeri 8 Lubuklinggau. The design used in this research is qualitative research. The resource persons in this study amounted to 3 people, consisting of 1 principal, 2 teachers. The data collection technique is interview technique. Data analysis used is data reduction, data display and conslusion drawing verification. Research results 1) The curriculum planning process can be adjusted to the needs and characteristics of students and the school environment. The implementation of MBS in independent curriculum planning cannot be separated from various challenges, such as limited resources, lack of teacher capacity, and changes in school culture. 2) The process of implementing the Independent Curriculum can be more effective and in accordance with the characteristics of students and the school environment. The Independent Curriculum provides high flexibility for schools in designing learning. 3) The evaluation carried out in the MBS context focuses more on real student learning outcomes, both in cognitive, affective, and psychomotor aspects. This is in line with the objectives of the Merdeka Curriculum to develop a holistic Pancasila learner profile. 4) The inhibiting factor in the implementation of School-Based Management (SBM) implementation is the lack of knowledge of education personnel about School-Based Management (SBM).